1987
DOI: 10.1111/j.1365-2621.1987.tb05880.x
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Analysis of Oil Samples Implicated in the Spanish Toxic Oil Syndrome

Abstract: A selected group of 195 oils from the Spanish "Toxic Oil" Syndrome (TOS) epidemic including 29 high-probability "case" and 64 "control" oils were examined to investigate the relationship between oil composition and the risk of TOS. As indicated by fatty acid and sterol patterns, the presence of rapeseed oil was significantly more prevalent in the case than in the control oils, but fatty acid anilides were the most useful markers of case-related samples. Anilides were detected in 62% of case oils and at lower c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…TOS-case samples were also analyzed by Bernert Jr. et al (1987) by an HPLC-UV method, but they could only quantify the 16:0, 18:l n-9 and 18:2 n-6 FAAs due to interferences in some samples with other oil components, so Figure 2 provides new information on the composition of FAAs in case-oils.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TOS-case samples were also analyzed by Bernert Jr. et al (1987) by an HPLC-UV method, but they could only quantify the 16:0, 18:l n-9 and 18:2 n-6 FAAs due to interferences in some samples with other oil components, so Figure 2 provides new information on the composition of FAAs in case-oils.…”
Section: Resultsmentioning
confidence: 99%
“…Authentic 10 case samples of TOS-associated oils (Bernert Jr. et al 1987) were kindly provided by Drs. M. Posada de la Paz and I. Abaitua, of the Fund for Health Research in Madrid, Spain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of TOS case-related oils has shown that a number of contaminants were formed through the reaction between components of the oil and the aniline denaturant (Hill et al, 1995;Bernert et al, 1987). The BIOMEDICAL CHROMATOGRAPHY Biomed.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the causal toxic agent remains unknown, as many substances which could potentially be the causative compound have been found in the implicated oils (4,5).…”
Section: Introductionmentioning
confidence: 99%